2018
DOI: 10.1186/s40246-018-0184-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of drug repurposing candidates based on a miRNA-mediated drug and pathway network for cardiac hypertrophy and acute myocardial infarction

Abstract: BackgroundCardiac hypertrophy and acute myocardial infarction (AMI) are two common heart diseases worldwide. However, research is needed into the exact pathogenesis and effective treatment strategies for these diseases. Recently, microRNAs (miRNAs) have been suggested to regulate the pathological pathways of heart disease, indicating a potential role in novel treatments.ResultsIn our study, we constructed a miRNA-gene-drug network and analyzed its topological features. We also identified some significantly dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The FoxO signaling pathway is involved in cell proliferation [46], and Wnt pathways are involved in the control of gene expression, cell behavior, cell adhesion, and cell polarity [47]. Taken together, these results and previous reports [48] have suggested that MAPK, FoxO, and Wnt signaling pathways are of great significance for normal physiological functioning of cardiomyocytes.…”
Section: The Mirna Characteristics Of Isoprenaline-induced Cardiac Hypertrophysupporting
confidence: 68%
“…The FoxO signaling pathway is involved in cell proliferation [46], and Wnt pathways are involved in the control of gene expression, cell behavior, cell adhesion, and cell polarity [47]. Taken together, these results and previous reports [48] have suggested that MAPK, FoxO, and Wnt signaling pathways are of great significance for normal physiological functioning of cardiomyocytes.…”
Section: The Mirna Characteristics Of Isoprenaline-induced Cardiac Hypertrophysupporting
confidence: 68%
“…In this way, one other promising alternative on which this review focuses is drug repurposing, also called repositioning (Mercorelli et al, 2018). This therapeutic shift is the subject of several studies in different pathologies including cancer (Sleire et al, 2017), heart diseases (Sun et al, 2018), Alzheimer's disease (Kim, 2015) or depression (Ebada, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another example in a recent study analyzed the topological features of a miRNAgene-drug network and identified miRNA-gene-drug triplets in cardiac hypertrophy and acute myocardial infarction; it later used the miRNA dysregulated pathways to identify novel drug repurposing candidates [49].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%